The Study Of Raskolnikov’s Inner Conflicts ‘In Fyodor Dostoevsky’s Crime and Punishment’ - Anna Ambarsari (1995)
Crime and Punishment was Fyodor Dostoevsky's first popularly successful novel after his imprisonment and exile. It is a complex story of a man's turbulent inner life and his relationship to others. In this work, Dostoevsky shows his talent of giving a profound insight into his characters. This study is an exposure of the central character (Raskolnikov)'s inner conflicts concerning with his crime. It is conducted to reveal the true nature of the character's crime, how he comes to such an act, and how he deals with it.